Climate Change and its Impacts on Photovoltaic Systems in each State of Brazil - Jurinic, Francesco; Farret, Felix Alberto (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Audacious plans are being implemented all over the world to mitigate climate change. Such plans require significant increases in the use of renewable and clean energy, making systems more vulnerable, as they are also impacted by climate change. This article seeks to elucidate future climate effects that may affect residential photovoltaic (PV) systems. In this article, the conditions of existing residential photovoltaic systems in Brazil are evaluated, representing a total of 818,149 installations, meaning 78% of all types of installations (commercial, rural, industrial, residential...). Here we also analyze the performance of the facilities for 59 years of meteorological data (1961 – 2020) and project forecasts of future climates for up to 100 years. It was found in the results that all Brazilian states already suffer large efficiency losses due to the high environmental temperature, which are gradually increasing, year after year, reaching a maximum average annual increase of more than 5 ºC in the north of the country. Even with perspectives of reduction in efficiency in this scenario of PV electricity generation, it is unlikely that such climate changes will threaten this sector in Brazil, as there is still a strong potential for use. The main reason for these predictions of increases in solar incidence is due to reductions in precipitation in all regions in the medium and long term.